A new adjunct in the differentiation of encephalitis and meningitis after negative cerebrospinal fluid culture: systemic inflammatory immune index - Arıkan, Cüneyt; Çınaroğlu, Osman Sezer; Efgan, Mehmet Göktuğ; Kanter, Efe; Bora, Ejder Saylav (The European Research Journal, 2023)
Objectives: Encephalitis and meningitis can have serious and potentially life-threatening consequences. This study aims to investigate whether the effects of systemic immune inflammation index (SII) and neutrophil/lymphocyte (N/L) ratio on differential diagnosis, severity, and clinical outcomes are superior to each other in patients diagnosed with encephalitis and meningitis in the emergency department. Methods: Patients aged 18 years and older who presented to the adult emergency department of the hospital and were diagnosed with meningitis or encephalitis between January and December 2022 were included in the study. Patients under 18 and those with missing data in their files were excluded from the study. N/L ratio, SII values, and other associated parameters were compared between the group with mortality and the group who survived both diseases. Results: There were significant differences in neutrophil, lymphocyte, N/L ratio, SII, and C-reactive protein (CRP) values between meningitis and encephalitis patients. N/L ratio and SII values were significantly lower in encephalitis patients than in meningitis patients. There was no significant difference in any of the parameters between surviving and deceased patients. Conclusions: Simple calculable ratios such as SII and N/L ratio can be a supportive parameter in the differential diagnosis of the disease. However, it has been observed that using these indices is not a useful tool in determining the severity and prognosis of patients with encephalitis and meningitis.